Fluoretação das águas de abastecimento público em um município com diferentes fontes de captação - Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP]; Barbosa, Tatiana Freitas [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Rovida, Tânia Adas Saliba; Saliba, Orlando [UNESP] (My University, 2011)
Maintaining the levels of fluoride ion in public water supply within the parameters of adequacy it becomes essential so the measure carries a greater impact on caries prevention and control, without increasing the prevalence of dental fluorosis. Thus, it is necessary a rigorous control of the process, avoiding the undesired effects at levels above recommended levels, as well as avoiding levels below the recommended that do not offer the highest benefit. The aim of this study was to analyze the content of fluoride in public water supply in the city of Birigui, SP, with different sources of supply, checking if the fluoride levels are within the recommended. The samples were collected monthly from points previously established, with the knowledge of the distribution network of water and identifying the amount and location of supply sources and water treatment plant. Analyses were performed in duplicate in the period from January to December of 2009, in the laboratory - NEPESCO - of the Dental School of Araçatuba, Univ Estadual Paulista – UNESP, using an ion analyzer coupled to a specific electrode for fluoride. Of the total samples (n = 512), 44% (n = 224) had adequate levels and 56% (n = 288) inadequate levels, 10% (n = 49) lower levels and 46% (n = 239) showed levels above the recommended. There were differences in results when comparing the analysis of different sources. The fluoride concentration in the majority of the samples from deep wells was classified as inadequate not offering the desired benefit, or exposing the population to the risk of dental fluorosis.

A manutenção dos teores do íon flúor nas águas de abastecimento público dentro dos parâmetros de adequação torna-se indispensável para que a medida exerça maior impacto na prevenção e no controle da cárie, sem aumentar a prevalência de fluorose dentária. Dessa forma, é necessário um rigoroso controle do processo, evitando-se os efeitos indesejados com teores acima do recomendado, bem como evitando teores abaixo do recomendado, que não oferecem o máximo benefício. O objetivo deste trabalho foi analisar o teor de flúor nas águas de abastecimento público do município de Birigui-SP, com diferentes fontes de abastecimento, averiguando se os teores adicionados encontram-se dentro dos parâmetros recomendados. As amostras foram coletadas mensalmente em pontos previamente estabelecidos, após o conhecimento da rede de distribuição de água e a identificação da quantidade e da localização de fontes de abastecimento e de estação de tratamento de água. As análises foram realizadas em duplicata no período de janeiro a dezembro de 2009, no laboratório NEPESCO da Faculdade de Odontologia de Araçatuba – UNESP, utilizando-se um analisador de íons acoplado a um eletrodo específico para flúor. Do total das amostras (n = 512), 44% (n = 224) apresentaram teores adequados e 56% (n = 288), inadequados, tendo-se 10% (n = 49) abaixo e 46% (n = 239) acima do recomendado. Houve diferença nos resultados, quando comparadas as análises de diferentes fontes de abastecimento. O teor de flúor na maioria das amostras dos poços profundos foi classificado como inadequado, não oferecendo o benefício desejado ou expondo a população ao risco da fluorose dental.
Fluoridation from public water supplies in a city with different sources of capture
Keywords: Fluoridation; Fluoride; Oral health; Water supply systems; Fluoretação; Flúor; Saúde bucal; Sistemas de abastecimento de água